Identification of Integron and Antibiotic Resistance Genes in Pseudomonas aeruginosa by Genetic Methods in Burn Patients at Al-Hussien Teaching Hospital in Al Samawah, Iraq - Neamah, Elaf Lateef; Mohemmad, Huda J.; Ghyadh, Bushra Ali; Jasim, Zaid Mohammed; Mandal, Amar Mousa (American Journal of Biology and Natural Sciences, 2026)
The skin’s defense mechanism against opportunistic infections is compromised by burn damage. One of the primary pathogens that colonize burn wounds and cause serious infections is Pseudomonas aeruginosa . Production of Extended Spectrum Beta-lactamase Enzymes (ESBLs) and Integron play a significant part in time wastage and selecting the best course of treatment. Using 16sRNA, sixteen P. aeruginosa isolates were detected by the conventional PCR technique. Amikacin (85%), Imipenem (70%), Tobramycin (65%), Azteronam, Cepfepime (63%), Ceftazidime (61%), were shown to have the greatest resistance levels, and the mordent resistance was demonstrated by Levofloxacin, Meropenem (55%), and Ciprofloxacin, Colistin (46%). The findings of the Double Disc Synergy Test (DDST) indicated that 10 (62.25%) among the isolates generated (ESBLs). All isolates were classified as Multidrug Resistance (MDR) 16(100%). The most common genotypes were Int-1 16(100%), BlaTEM 16(100%), and Bla CTX-M 13 (81.2%). Because Enterobacteriaceae produced a large number of ESBL and Integron Class-1 genes, Slowing the spread of antibiotic-resistant illnesses requires the application of high standards in both public health and laboratory practices.